The Influence of Climate Change on Paddy Production in West Sumatra - Andreas Sitanggang (CV Projurnal Mitra Publikasi, 2025)
Paddy is a food crop commodity that produces rice which is the food most consumed by the population in Indonesia. Paddy is produced in almost all regions in Indonesia, one of which is West Sumatra. West Sumatra is one of the largest paddy-producing regions in Indonesia, however, in recent years, paddy production in West Sumatra has experienced a significant decline. This research aims to determine the climate factors that influence paddy production in West Sumatra. The type of data used in this research is secondary data including data on paddy production, rainfall, number of rainy days, temperature, humidity, wind speed, and air pressure in West Sumatra Province in 2013 - 2023. The data analysis used in this research is simple linear regression analysis. The research results show that rainfall, number of rainy days, and temperature have a significant effect on paddy production in West Sumatra, while humidity, wind speed, and air pressure do not have a significant effect on paddy production in West Sumatra.